Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Massa Coffee Shop Bandung - Putri Oktaviani Devi; Ramayani Yusuf (Ekonomis: Journal of Economics and Business, 2022)
The aim of this research is to see how the quality of service affects customer satisfaction at Massa Coffee Shop in Bandung. With a total of 70 respondents, this study was done by doing the observation technique and customer dispersion of Massa Coffee Shop Bandung. In this study, snowball sampling was utilized as a sample method. The validity, reliability, and normalcy tests, as well as the basic linear regression test, the T test (hypothesis test), the F test (together test), and the R2 test, were all employed in this study (test of determination). According to research, service quality has a 62,1% significant effect on customer satisfaction, with the remaining 37,9% coming from other variables not included in the research.